ANISOTROPY OF MAGNETIC SUSCEPTIBILITY OF HEATED ROCKS - Henry B.; Jordanova D.; Jordanova N.; Souque C.; Robion P. (My University, 2003)
Heating produces changes, which does not always correspond to simple enhancement of the magnetic fabric. Two methods are proposed to determine the anisotropy of magnetic susceptibility of the ferrimagnetic minerals formed or that have disappeared by chemical change during successive heating. The first diagonalizes the tensor from the difference between each tensor term before and after heating. The second employs linear regression for each tensor term made with the values obtained throughout a thermal treatment. When the same magnetic fabric is obtained from several thermal steps, it cannot be related to randomly oriented ferrimagnetic minerals. Instead, the newly formed fabric must be related to characteristics of the pre-existing rock. By comparing this ferrimagnetic minerals fabric with the initial whole rock fabric, we can distinguish cases where heating simply enhances pre-existing fabric from those where thermal treatment induces a different fabric. Relative to the pre-heating fabric, this different fabric may simply be an inverse fabric or one whose principal susceptibility axes are oriented in a different direction, related to petrostructural elements other than those defining the initial fabric.
Keywords: ANISOTROPY; MAGNETIC SUSCEPTIBILITY; THERMAL TREATMENT; FERRIMAGNETIC MINERALS